2009
DOI: 10.1091/mbc.e08-07-0707
|View full text |Cite
|
Sign up to set email alerts
|

The Ldb1 and Ldb2 Transcriptional Cofactors Interact with the Ste20-like Kinase SLK and Regulate Cell Migration

Abstract: Cell migration involves a multitude of signals that converge on cytoskeletal reorganization, essential for development, immune responses, and tissue repair. Here, we show that the microtubule-associated Ste20 kinase SLK, required for cell migration, interacts with the LIM domain binding transcriptional cofactor proteins Ldb1/CLIM2 and Ldb2/CLIM1/NLI. We demonstrate that Ldb1 and 2 bind directly to the SLK carboxy-terminal AT1-46 homology domain in vitro and in vivo. We find that Ldb1 and -2 colocalize with SLK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 22 publications
1
44
0
Order By: Relevance
“…However, in accordance with the derived dissociation constants of this structure, additional associations appear to be required to achieve efficient dimerization [77]. Interestingly, SLK has been shown to contain dimerization domains adjacent to the kinase region, where demonstrated LDB1/2-SLK binding [76,77]. Further investigation into this transhomodimerization has led to the discovery of two novel SLK phosphorylation sites namely S189 and T183, in which T183 was identified as an important site for SLK autophosphorylation [77].…”
Section: Slk Auto-phosphorylation and Substratesmentioning
confidence: 58%
See 3 more Smart Citations
“…However, in accordance with the derived dissociation constants of this structure, additional associations appear to be required to achieve efficient dimerization [77]. Interestingly, SLK has been shown to contain dimerization domains adjacent to the kinase region, where demonstrated LDB1/2-SLK binding [76,77]. Further investigation into this transhomodimerization has led to the discovery of two novel SLK phosphorylation sites namely S189 and T183, in which T183 was identified as an important site for SLK autophosphorylation [77].…”
Section: Slk Auto-phosphorylation and Substratesmentioning
confidence: 58%
“…Recent studies have shown that SLK localizes to the leading edge of migrating cells with vinculin and paxillin as well as with the LIM domain binding proteins, LDB1 and LDB2 following scratch-wounding of a confluent monolayer of fibroblasts [69,76,78]. This localization has been shown to occur in response to both the induction of wound-healing as well as the activation of the receptor tyrosine kinase ErbB2 [69,79].…”
Section: Involvement In Signaling and Migrationmentioning
confidence: 99%
See 2 more Smart Citations
“…124 SLK, which is similar to LOK, can regulate focal adhesion turnover through unknown mechanism that involves FAK. [125][126][127] The GCK-VIII subfamily member TAO2 is a mitogen-activated protein kinase kinase kinase which associates with and activates MAPK/extracellular signal-regulated kinase kinase 3 (MEK3) and MEK6 to activate p38. 128 Since p38 regulates the expression of inflammatory cytokines, TAO2 may be considered for therapeutic targeting for diseases such as autoimmunity.…”
Section: Other Gcks Relevant To Immune Regulationmentioning
confidence: 99%